LEVERAGING PICTURES FOR ELT: A SYSTEMATIC REVIEW - Syakira Desiya; Nasiha Amirotul Khoiriyah; Nafan Tarihoran (Adisam Publisher, 2025)
The integration of pictures in English Language Teaching (ELT) has been widely acknowledged as an effective strategy to enhance language acquisition. This systematic review aims to synthesize existing empirical studies on the use of pictures in English Language Teaching (ELT), focusing on their effectiveness, influencing factors, and implementation challenges. Following the PRISMA guidelines, 30 studies from reputable academic databases, including PubMed, Mendeley, ScienceDirect, Taylor & Francis, and Connected Paper, were analyzed for the period from 2020 to 2025. The findings suggest that pictures play a crucial role in enhancing vocabulary acquisition, writing, reading comprehension, and speaking skills. Additionally, their effectiveness is shaped by learner characteristics, the type of visual media, instructional strategies, technology integration, and socio-geographical contexts. The study also highlights that using pictures fosters student engagement and facilitates meaningful learning experiences, especially when combined with digital tools. However, challenges such as limited infrastructure, inadequate teacher training, and insufficient visual representation in textbooks persist in specific contexts. The review highlights the importance of adaptive and technology-driven approaches in enhancing the role of pictures in English Language Teaching (ELT), thereby ensuring their relevance across diverse learning environments.